Respostas
respondido por:
14
√3 + √6·√2 - √27
√3 + √12 - √27
√3 + √3 · √4 - √3 · √9
√3 + 2√3 - 3√3
3√3 - 3√3
0
Resposta: c) 0
Espero ter ajudado
√3 + √12 - √27
√3 + √3 · √4 - √3 · √9
√3 + 2√3 - 3√3
3√3 - 3√3
0
Resposta: c) 0
Espero ter ajudado
respondido por:
2
Olá!! Tudo bem?
Resposta: alternativa C, 0
Explicação passo-a-passo:
√3 + √6 . √2 - √27 =
√3 + √12 - √27 =
√3 + √3 · √4 - √3 · √9 = <== (√12 e √27)
√3 + 2√3 - 3√3 =
3√3 - 3√3 =
0
ESPERO TER AJUDADO!!
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás